A Novel Transcriptional Regulator HbERF6 Regulates the HbCIPK2-Coordinated Pathway Conferring Salt Tolerance in Halophytic Hordeum brevisubulatum - Jiang, Ying; Zhang, Haiwen; Li, Yang; Chang, Congcong; Wang, Yunxiao; Feng, Hao; Li, Ruifen (Frontiers in Plant Science, 2022)
Halophytic Hordeum brevisubulatum is a perennial grass which has evolved many distinctive salt-adaptive mechanisms. Our previous studies indicated it could thrive under salt stress through keeping better K+ and Na+ homeostasis. Stress-responsive HbCIPK2 can phosphorylate K+ channel HbVGKC1 and Na+ transporter HbSOS1L to prevent Na+ accumulation and K+ reduction, which pathway was not detected in glycophytic plants. Here we cloned inducible promoter of HbCIPK2 by genome-walking, and identified a novel transcriptional regulator HbERF6 through yeast one-hybrid screening. HbERF6 functioned as transcription factor which can bind to the GCC box of HbCIPK2 promoter to activate its expression. HbERF6 transgenic lines in Arabidopsis improved salt tolerance compared with wild type, and induced the expression of many stress genes including AtCIPK24 (SOS2), resulting in K+/Na+ homeostasis to enhance salt tolerance. All the results confirmed the inducible function of HbERF6 for CIPK genes during salt resistance. This regulatory network that integrates transcriptional regulation and post-translation modification will unravel novel salt stress-responsive mechanism, highlighting the value and utilization of halophytic resource.